Customer Delight Measurement in Halal Cosmetics Industry in Malaysia: The Relationship between Functional Values, Epistemic Values and Customer Emotions towards Customer Delight - Yeo Bee Li; Rozita Naina Mohamed; Shafinar Ismail; Mohd Khirzan Badzli A. Rahman; Siti Asiah Md Shahid (International Journal of Supply Chain Management, 2018)
Providing and maintaining customer emotion experience and satisfaction are the biggest contemporary challenges of management in Halal cosmetics industry. While customer satisfaction measures the perception of the customers, customer delight is the measure to success. Delighted customers are loyal and more valuable as they will help the organisation to compete with the competitors. The objective of this article is to present a conceptual framework to examine the role of functional values (Halal product attributes and reference price), epistemic values (Halal visual packaging design) in establishing positive customer emotion experience in the customers mind for Halal cosmetics products and ultimately achieving customer delight. The well-established Holbrook consumer value model was applied to test its validity and robustness in the Halal cosmetics products context. A self-administered, 5-points Likert scale questionnaire was distributed to selected retail outlets throughout the states in Malaysia. The findings indicated that functional values and epistemic values are insignificant in creating positive customer emotion experience, but customer emotion experience shows significant relationship with customer delight for Halal cosmetics products. In view of the relationship between these variables can assist the providers to improve their product offerings and competitive strategies.